(untitled) (Al-Academy, 2025)
The problem of the study intiteld (Strategy of invention and innovation in products design) was present of how can the strategy of invention & innovation contribute in effect way products design , research importance lies to identify of most important strategies which followed by industries to meet needs & wishes of the consumers in superiority & success, the aim ot the research is to piano the effect limit ot invention & innovation strategy possibility to subtract new products to the markets and insertion the research importance to the invention, innovation and competition areas, the research limits included products users differ their segments, cultures and physical potential. Doctrinarian Framework contains three sections, the first one contains the subject of invention & innovation strategy & communication process. The second subject singled to study the invention & innovation object in design and their effect on consumer The third subject singled to study the competetion object and its role to present invention & innovation products. The important results which the research reaches are : 1) The designer derives his invention design idea through memory and imaginary, with out memory he cant imagine, and with out imagination he cant remember. 2) Innovation not limited only on process design notify exceeded it on function and technique of the design itself, invention being can’t predict it, or control it. 3) Through featurity, superiority and competition the product firms development and efficiency luxurious dividends.